2021
DOI: 10.1007/s12016-021-08868-z
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Features, Immunopathogenesis, and Therapeutic Strategies in Vitiligo

Abstract: Vitiligo is an autoimmune disease of the skin characterized by epidermal melanocyte loss resulting in white patches, with an approximate prevalence of 0.5-2% worldwide. Several precipitating factors by chemical exposure and skin injury present commonly in patients with vitiligo. Although the diagnosis appears to be straightforward for the distinct clinical phenotype and specific histological features, vitiligo provides many challenges including chronicity, treatment resistance, frequent relapse, associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 213 publications
(353 reference statements)
1
46
0
2
Order By: Relevance
“…The patients involved in this study were consistent with the diagnostic criteria of vitiligo. 2 Systemic therapy (glucocorticoids, immunosuppressive agents, and biological agents), phototherapy, or topical therapy (corticosteroid agents, vitamin D analogs, and tacrolimus) were not used within 3 months before the collection of specimens. No congenital diseases, acquired autoimmune diseases, other immune-related diseases, coagulation disorder, or other inappropriate surgical diseases were reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients involved in this study were consistent with the diagnostic criteria of vitiligo. 2 Systemic therapy (glucocorticoids, immunosuppressive agents, and biological agents), phototherapy, or topical therapy (corticosteroid agents, vitamin D analogs, and tacrolimus) were not used within 3 months before the collection of specimens. No congenital diseases, acquired autoimmune diseases, other immune-related diseases, coagulation disorder, or other inappropriate surgical diseases were reported.…”
Section: Methodsmentioning
confidence: 99%
“… 1 The estimated global prevalence of vitiligo varies from 0.5% to 2%. 2 The clinical classification of vitiligo is generally divided into non-segmental, segmental, mixed and undetermined types. The former includes generalized, universal, acrofacial and mucosal types.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is classified as an autoimmune disease having a genetic basis and an association with environmental factors, including chemical triggers, skin injury, sunburn, and virus infection. Vitiligo is considered to develop as a result of metabolic, oxidative stress, and cell detachment abnormalities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…10−12 However, an adaptive immune response inducing melanocyte destruction mediated by IFN-γ-JAK/STAT-chemokine signaling is being recognized increasingly as a main reason for vitiligo. 13,14 The IFN-γchemokine signaling axis is responsible for recruiting autoimmune cells to kill melanocytes, which involves Janus kinase (JAK) 1 and 2, chemokine (C-X-C motif) ligand (CXCL) 9 and 10, and phospho-signal transducers and activators of transcription (p-STAT). It is reported that the biomarker for the progression of vitiligo is chemokine CXCL10, which is identified as playing a critical role in both the progression and maintenance of vitiligo.…”
mentioning
confidence: 99%
“…Therefore, the absolute configuration of 2 (seritranin B) was determined as 7Z,10S. Quantum chemical calculations showed (7Z,10S)-2 exhibited an excellent linear correlation between the experimental and calculated 13 C and 1 H NMR chemical shifts (R 2 : C 0.99868; 1 H 0.99580) (Figure S2C and D, Supporting Information). In addition, the CMAE and MD of 13 C for (7Z,10S)-2 were 1.78 and 4.90 (Table S5, Supporting Information), which conformed to the standard MAE < 2.2 and MD < 5.…”
mentioning
confidence: 99%